Percutaneous trigeminal rhizotomy. Treatment of trigeminal neuralgia secondary to multiple sclerosis. - Brett, D; Ferguson, G; Ebers, G; Paty, D (1982)
Eight patients with trigeminal neuralgia secondary to multiple sclerosis have been treated with percutaneous trigeminal radiofrequency rhizotomy after failure of medical therapy. Excellent results were obtained with this procedure, which seems ideally suited to these patients who tolerate carbamazepine poorly.